LaMacchia Will Be Arraigned Friday - Anonymous (Online Ethics Center, 2006)
An article about the indictment and arraignment of LaMacchia, along with details on how MIT officials discovered the file-sharing network.
Case Study / Scenario
Keywords: Security; Privacy and Surveillance; Ethics and Society